Evaluation of the hemostatic efficacy and safety of an absorbable hemostatic powder based on a porcine intracranial hemorrhage model - Shi, Jiali; Zhou, Yun; Fu, Yang; Wang, Jin (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionThis work aimed to evaluate the hemostatic efficacy and safety of an absorbable hemostatic powder in intracranial hemorrhage of porcine model.MethodAbsorbable hemostatic powder was prepared from potato starch via mulsification and cross-linking technology, followed by structural characterization. An intracranial and extracranial injury hemorrhage in Bama miniature pigs’ model was established to evaluate the safety and effectiveness of the absorbable hemostatic powder. The biophysical characteristics of the absorbable hemostatic powder were compared with the control group and marketed product.ResultsAbsorbable hemostatic powder is a multi-microsphere with a spatial reticular microstructure with a porosity of 61.77%. Its water absorption rate reached over 1,200%. Animal research results showed that the hemostasis time and bleeding volume of the absorbable hemostatic powder were 73.50 ± 29.08 s and 3.90 ± 2.09 g, respectively. Compared with the model control group, both were significantly reduced (P < 0.01). Its hemostatic efficacy was comparable to that of the currently marketed product, but the required dosage was significantly lower (P < 0.01), being half that of the marketed products. The degradation study demonstrated that the absorbable hemostatic powder was almost completely degraded in the in vitro simulated environment within 48 h, and the degradation and absorption process was essentially completed after 42 days of implantation in the body. At the same time, no abnormalities were observed in the general signs, blood coagulation indicators, and pathological examination of the miniature pigs during the research process.DiscussionThe conclusion indicated that the absorbable hemostatic powder was safe and effective in neurosurgical applications. Its porous structure design combines the advantages of rapid hemostasis and biocompatibility, providing a new idea for the development of clinical hemostatic materials.